Hybrid Organic–Inorganic Materials Prepared by Sol–Gel and Sol–Gel-Coating Method for Biomedical Use: Study and Synthetic Review of Synthesis and Properties - Barrino, Federico (Coatings (Basel), 2024)
The need to improve the expectancy and quality of life of subjects affected by disabling pathologies that require the replacement or regeneration of tissues or parts of the body has fueled the development of innovative, better-performing materials that are capable of integrating into and being tolerated by body tissues. Materials with these characteristics, i.e., bio-functionality, bio-safety, and biocompatibility, are defined as biomaterials. One of the many methods for producing such materials is the sol–gel technique. This process is mainly used for the preparation of ceramic oxides at low temperatures, through hydrolysis and polycondensation reactions of organometallic compounds within a hydroalcoholic solution. This study is based on a specific type of biomaterial: organic–inorganic hybrids. The aim of this study is to provide an overview of the advantages and disadvantages of the sol–gel technique, as well as describe the preparation and chemical and biological characterization, uses, and future prospects of these biomaterials. In particular, the use of plant drugs as organic components of the hybrid material is the innovation of this manuscript. The biological properties of plant extracts are numerous, and for this reason, they deserve great attention from the scientific community.